Liūdesio konceptualizavimas lietuvių kalboje - Papaurėlytė, Silvija (Kalbotyra, 2002)
The goal of the article is to describe a part of the concept, represented in the Lithuanian language by the word liūdesys ‘sadness’, based on different samples of usage.The work is based on the method of conceptual analysis. Conceptual/cognitive metaphors disclose a part of the content of the concept. A linguist is interested in the combination of a word of abstract meaning and a verb of figurative meaning since they give a great deal of information about the qualities of an object belonging to the abstract sphere and motivate corresponding conceptual metaphors. The conceptual analysis formalises what exists in collective subconsciousness and is expressed in speech.Having analysed a number of ways of representing the concept of sadness in the Lithuanian language, we can point out the basic tendencies of realising the concept: sadness as a thing, sadness as a cavity, sadness as a liquid, sadness as gas, sadness as a burden, sadness as a cloak, sadness as a natural calamity (fire, rain, mist), sadness as an illness, sadness as a living being (human, beast, enemy, sovereign).Consequently, sadness is an intensive emotional state in the world outlook of the Lithuanian language, which is being controlled and which at the same time is characterised by a lack of control and the ability to contain the emotion felt. This is a negative emotional state as it is linked with the subjects and objects that can harm people (illness, beast, enemy, burden), although neutral or even positive estimation of sadness is also possible.What is being reflected in linguistic combinations of words and somatic idioms correlates with the analysis of this emotional state presented by psychologists.